If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -45 = 4(x + -2) + -9 Combine like terms: 16 + -45 = -29 -29 = 4(x + -2) + -9 Reorder the terms: -29 = 4(-2 + x) + -9 -29 = (-2 * 4 + x * 4) + -9 -29 = (-8 + 4x) + -9 Reorder the terms: -29 = -8 + -9 + 4x Combine like terms: -8 + -9 = -17 -29 = -17 + 4x Solving -29 = -17 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -29 + -4x = -17 + 4x + -4x Combine like terms: 4x + -4x = 0 -29 + -4x = -17 + 0 -29 + -4x = -17 Add '29' to each side of the equation. -29 + 29 + -4x = -17 + 29 Combine like terms: -29 + 29 = 0 0 + -4x = -17 + 29 -4x = -17 + 29 Combine like terms: -17 + 29 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| b=c+24 | | -8y+3y-(10)+2y=11 | | 5+(n+9)=-3 | | 15=2t+.806t | | 25+50h=8 | | 3y^2+27y+60=0 | | 3(x+2)-10(x+10)=-7-8 | | 4t=2(7x+15) | | 6(3x+7)=3x+2-5x | | 3+5h=5 | | 10(x-2)=2(x+9) | | 34-0.5d=26 | | 2.1(a+2)=2.1a+4.2 | | 4-4(x-2)=-1+3(x-5+2) | | 3n-6-6+2n=4n-12 | | 0=-4x+21-x^2 | | 2x(5.83)=x(5.83) | | 5x=8(6x-1)-35 | | 4x^3+12x^2+2=0 | | 11-(-10)-5/6= | | 4[2-3(2x+4)]=5x | | (y-6)-(5y-7)= | | log(x)=1.9 | | y=9x^2-36 | | -40=6x+8 | | 5(1x+7)=20 | | (y-5)-(5y-7)= | | 3x+10=15x-8 | | 5(-2x+8)=-50 | | 4(2+2)= | | 2x+3-5x+7=1 | | 17y^2+5y-126=0 |